2022
DOI: 10.17507/jltr.1305.12
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Attitudes Towards Applying Cooperative Learning Strategy at Amman Arab University

Abstract: The current research aimed at discussing the use of the Cooperative Learning strategy and its applications in AAU English courses. The researchers collected the data from several online resources and books. A questionnaire was developed as another assessment tool and was distributed to Amman Arab University students. The sample was 600 students from all faculties. In addition to conducting interviews with English Doctors at Amman Arab University to inquire about their teaching strategies and methods and the ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…This observation suggests a potential approach for enhancing students ease and self-assurance in group settings. Furthermore, it aligns well with the existing body of research that emphasizes the positive impact of cooperative learning strategies on the enhancement of social well-being (Zaman, 2020;Khalifeh et al, 2022;Troop-Gordon et al, 2021). Teachers and policymakers may be able to address this aspect of students' social well-being by concentrating on interventions that support cooperative learning.…”
Section: Problemsupporting
confidence: 71%
See 2 more Smart Citations
“…This observation suggests a potential approach for enhancing students ease and self-assurance in group settings. Furthermore, it aligns well with the existing body of research that emphasizes the positive impact of cooperative learning strategies on the enhancement of social well-being (Zaman, 2020;Khalifeh et al, 2022;Troop-Gordon et al, 2021). Teachers and policymakers may be able to address this aspect of students' social well-being by concentrating on interventions that support cooperative learning.…”
Section: Problemsupporting
confidence: 71%
“…Consistent with the findings of Woodgate et al (2019), peer support has been shown to promote a favorable mindset and a sense of embracing. This promotes authentic relationships and cooperative efforts among peers (Zaman, 2020;Khalifeh et al, 2022). Tilley et al (2020) suggest that peer support serves as a forum for students to exchange experiences, seek help, and implement strategies to resolve bullying situations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3. The arithmetic mean for the economic side was (32,715), standard deviation (7,031), hypothetical mean (12), and the calculated T-value amounted to (11,496), which is greater than the tabular value of (0.161) at the significance level (0.05) and the degree of freedom (131). This means that the research sample prefers the economic aspect.…”
Section: It Is Evident From the Above Table Thatmentioning
confidence: 74%
“…He also must explain the basic strategic concepts, and then inspect the work of cooperative groups and teach students work skills. Also, assessing the learning of the group students and providing the appropriate conditions for cooperative learning [32]. Choosing the topic and the main headings, defining objectives, as well as organizing and managing Al-Qaeda.…”
Section: The Role Of the Teacher (Professor) In Cooperative Educationmentioning
confidence: 99%